Combustion and grindability characteristics of palm kernel shells torrefied in a pilot-scale installation. (March 2020) - Junga, Robert; Pospolita, Janusz; Niemiec, Patrycja
Abstract: The main goal of this paper is the evaluation of combustion and grindability of torrefied palm kernel shells (PKS) obtained in a pilot-scale installation. The torrefied samples were prepared in different time conditions and temperatures, ranged from 220 to 300 °C. The physico-chemical properties were identified. Thermogravimetric analyses (TG-DTA) were used for characterization of the combustion performance and evaluation of the activation energy E α . The grindability of the pre-treated biofuel was investigated in a pilot-scale, coal bowl-roller milling unit. The results were compared to those of the raw PKS and bituminous coal. Torrefaction was found to increase carbon C content and HHV by 2–33 and 2–26%, respectively. Moreover, the combustion characteristics of the torrefied PKS samples are close to each other, but the ignition and burn-out temperatures differ significantly. The torrefaction changes the activation energy E α and it approaches the E α values to those of coal. Both the torrefaction temperature and residence time significantly affect the grindability. The grinding effect of PKS torrefied at 220 °C reached the value of 10%, whereas after torrefaction at 300 °C it doubled. The torrefaction considerably improves the properties and combustion behaviour of biomass, which is a good predictor for burning and co-burning in industrial units. Highlights: Torrefaction increase the higher heating value of the palm kernel shells. Ignition and burn-out temperature of the torreffied PKS samples differ significantly. Torrefaction temperature and residence time improves the grindability. The activation energy decreased with the carbonization degree increase.